2019
DOI: 10.1109/access.2019.2917698
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Computer Architecture Simulation Techniques and Tools

Abstract: Computer architecture simulators play an important role in advancing computer architecture research. With wider research directions and the increased number of simulators that have been developed, it becomes harder to choose a particular simulator to use. This paper reviews the fundamentals of different computer architecture simulation techniques. It also surveys many computer architecture simulators and classifies them into different groups based on their simulation models. Comparing computer architecture sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 118 publications
0
30
0
2
Order By: Relevance
“…Since Desikan's work, several simulators have been created along a validation effort to evaluate their accuracy. In Akram et al's research, 31 the authors evaluated and compared the gem5, 32 Multi2Sim, 33 MARSSx86, 34 PTLsim, 35 Sniper, 6 and ZSim 5 simulators. After thorough characterization of the simulators, the authors tested single core and multiprogrammed workloads on each simulator.…”
Section: Related Workmentioning
confidence: 99%
“…Since Desikan's work, several simulators have been created along a validation effort to evaluate their accuracy. In Akram et al's research, 31 the authors evaluated and compared the gem5, 32 Multi2Sim, 33 MARSSx86, 34 PTLsim, 35 Sniper, 6 and ZSim 5 simulators. After thorough characterization of the simulators, the authors tested single core and multiprogrammed workloads on each simulator.…”
Section: Related Workmentioning
confidence: 99%
“…Prior work has surveyed many existing simulators [23], [24], with classifications based on traditional usage within the computer architecture research community as well as through an educational and pedagogical point of view [25]- [27], with some surveys proposing criteria for the evaluation of their suitability for teaching courses in computer architecture. Within the proposed criteria, the generator-based approach demonstrated in this work would be considered under the "Advanced Architecture (AA)" category with "Design Support.…”
Section: Generator-based Hardware Designmentioning
confidence: 99%
“…It was demonstrated by [10] that proper validation and calibration of simulator is very important for its accuracy. Accuracy evaluation made during this study showed that the least error in accuracy is achieved by simulators Sniper and ZSim, which have been validated against real hardware.…”
Section: Related Workmentioning
confidence: 99%